Actant Pattern in Some of Masnavi's Theological Narratives (Based on Algirdas Greimasâ Theory of Actant Pattern) - j Moshayedi; r azad (متن شناسی ادب فارسی, 2011)
In narratology, characters are considered as part of overall structure of text and are subject to predetermined actions. Thus, for analyzing characters, first of all, a pattern of their action area should be gained. Algirdas Julien Greimas is among those narratologists who gained such a pattern. Greimas believes his actant pattern is universal and compatible with any kind of narrative. On the other hand, the theme of narrative can somehow affect its structure. In this article, with respect to universality of Greimasâ pattern and its compatibility with any kind of narrative, some narratives of first and second book of Masnavi which have theological theme were selected to show what would happen during the confrontation of theological narratives and actant pattern as a part of structure, and through this confrontation a new window will be opened so that we can gain a novel and different view about some of theological narratives of Masnavi. What is emphasized as the result of this research are changes which take place due to the theological theme of narratives, especially in the action area of halter and helper. Proportional to their theological ideas, actants are sometimes aware of these changes and sometimes act unconsciously. Also, on the basis of Greimasâ theory and Actions Monotheism idea, the fundamental binary opposition in selected narratives of Man and God is considered as the real and unreal subjects whose objects can be in the same or opposite direction.